Temperature Control System on Aquascape using On-Off Control - Widodo; Setiawan, Rudi (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2021)
Every human being has a feeling of saturation in carrying out his daily activities. There are many ways you can do to get rid of boredom, one of which is by doing hobbies that we like. Currently there are many hobbies that can be done, one of which is a hobby of decorating an aquarium (Aquascape) by using stones, wood, sand and using water plants. Which is starting to be of interest to various circles of society. For Aquascape owners, sometimes their daily activities are busy. In fact, these other activities can take up to days. The solution to the problem of fan negligence when maintaining the Aquascape is to build an aquarium system that can adjust the lighting periodically as needed, stabilizing the water temperature in the aquarium